Supplementary Data from Prophylactic In Vivo Hematopoietic Stem Cell Gene Therapy with an Immune Checkpoint Inhibitor Reverses Tumor Growth in Syngeneic Mouse Tumor Models - Li,C; Course,MM; McNeish,IA; Drescher,CW; Valdmanis,PN; Lieber,A (2023)
Supplementary Fig. S1. Rat Neu is expressed in MMC cells. Supplementary Fig. S2. Gating strategy used for immunophenotyping. Supplementary Fig. S3. Immunophenotyping of GFP+ cells in the bone marrow and spleen (MMC model). Supplementary Fig.S4. GFP expression in tumor-infiltrating leukocytes after in vivo HSPC transduction (TC-1 model). Supplementary Fig. S5. Validation of miR-423-5p expression by Northern blot. Supplementary Fig.S6. miRNA423-5p expression in humans. Supplementary Fig. S7. Autoimmune reactions in animals sacrificed at day 17 at the peak of aPDL1-gamma1, before reversal of tumor growth. Supplementary Fig. S8. Effect of anti-PDL1 monoclonal antibody therapy in neu-transgenic mice with MMC tumors. Supplementary Fig. S9. Effect of in vivo HSC transduction on hemopoiesis. Suppl. Methods